Phytochemical composition and antimicrobial activity of essential oil from the leaves of Peganum harmala L. in southern Algeria. - Abderrahmane Ghillace; Ourida Chouitah; Fatima Zohra Kiari; Zineb Fergoug; Zineeddine Daikh (Acta Biologica Slovenica)
Medicinal plants have a wide use in traditional medicine. For this our study aims to valorize medicinal and aromatic plants of the Algerian flora, for this reason we determined the phytochemical composition and antimicrobial activity of essential oil of  Peganum harmala in two different southern regions. Phytochemical screening reveals the presence of flavonoids, alkaloids, saponins, tannins, glycosides, terpenoids and steroids and the absence of anthraquinons. The essential oil of P.harmala leaves was analyzed by GC-MS. The results revealed the presence of 55 and 47 compounds with a yield of 0.217 % and 0.211 %. These essential oils contain the same major components for Bougtob region Carvone (21.15%), Phytol (17.41%), Carbamic acid (3.52%), Lauric acid (2.10%), and Thymol (1.77%) and Tetrapentacontane (1.32%). For the region of Mechria, Phytol (10.24%), Carvone (5.92 %), Tetrapentacontane (2.80%), Phytone (2.18%), Butylated Hydroxytoluene (1.48%), Lauric acid (1.39%). The essential oils which were tested showed variable degrees of antimicrobial activity. In general, Gram-positive bacteria and fungus were found to be more sensitive to the essential oils than Gram-negative bacteria.